The chemicals of life : enzymes, vitamins, hormones - Asimov, Isaac (New York, Abelard-Schuman, 1954)
Discusses proteins, enzymes, vitamins, and hormones and explains what they do and how they work within the body to maintain life.
includes index.
Keywords: Biochemistry; Biochemistry